SERUM ZINC AND COPPER LEVELS IN BENIGN AND MALIGNANT LESIONS OF PROSTATE - C. REKHA; V. PRAVEENA (International Journal of Pharma and Bio Sciences, 2014)
To estimate the levels of serum zinc, copper and prostate specific antigen in patients with benign prostatic hyperplasia (BPH) and prostate carcinoma (PCa) and to correlate their levels as screening test in the diagnosis of prostate neoplasms. Serum zinc and copper were estimated in 25 patients of BPH and 18 patients with PCa over a period of one year. All patients were males and aged between 55 and 75 years. Age matched 25 male patients without BPH or PCa were taken as controls and serum zinc and copper were estimated in them also. An attempt was made to correlate the zinc/copper levels ratio in both diseases. The mean levels of serum zinc were raised significantly in BPH (152 ± 25.94 µg/dl) and lowered significantly in PCa (84.8 ± 33.11µg/dl) than in controls (110.0 ± 20.20µg/dl), p < 0.001. The mean levels of serum copper were raised significantly in both BPH (179.10 ± 55.19 µg/dl) and in PCa (154.10 ± 45.45 µg/dl) than in controls (112.00 ± 17.95 µg/dl), p <0.05. Prostate specific antigen was increased significantly in PCa (47.18 ±8.53 ng/ml) than in BPH (6.50 ± 2.25 ng/ml) and controls (2.78 ± 0.73 ng/ml), p <0.05. The mean value of copper/zinc ratio was significantly more in PCa (2.08 ± 0.81) than in BPH 1.23 ± 0.55) and controls (1.04 ± 0.19), p <0.05.The significantly high level of serum zinc in BPH and low level in PCa, along with high copper/zinc ratio and markedly increased levels of prostate specific antigen in PCa helps to differentiate BPH from PCa.